The UK public’s trust in tobacco industry involvement in science – an experimental survey - Legg, Tess; Bero, Lisa; Lewandowsky, Stephan (Frontiers in Communication, 2024)
Introduction Despite the tobacco industry’s (TI) decades-long history of manipulating science, Philip Morris International (PMI) now frames itself as a benevolent funder of science and, in 2017, launched a new scientific organisation, the Foundation for a Smoke-Free World (FSFW). With concerns mounting that PMI’s actions are echoing historical TI influence on science, we aimed to understand the extent to which the public trusts PMI’s involvement in science, and whether channelling funds through a third-party organisation affects these levels of trust. Methods Through a representative survey of the UK public (n=1580) we investigated trust in direct (PMI), indirect (FSFW), and no (Cancer Research UK) TI involvement in science. Conservative worldview was investigated as a possible predictor of trust. Structural equation modelling was used to explore associations between variables. Results Although PMI was significantly less trusted than FSFW and Cancer Research UK, the public did not completely distrust it as a scientific source. Trust in FSFW’s involvement in science was higher before participants understood its TI funding. People with conservative worldviews demonstrated greater trust in TI involvement in science. Discussion The UK public needs to be better informed that the TI is not a trustworthy scientific source. Since channelling TI research funds through a third party increases the perceived trustworthiness of its science, steps to prevent such relationships are warranted. People with conservative leanings hold concerning views on TI involvement in science, which may be particularly hard to correct.